Linguistic Landscape and Cultural Approach through Minangkabau and Malay Language as Election Campaign Strategies - Oktavianus Oktavianus; Indirawati Zahid; Ferdinal Ferdinal; Zulprianto Zulprianto (Jurnal Gramatika, 2024)
Politicians' use of language as part of a cultural approach to influence voters is visible during political campaigns in Minangkabau (West Sumatra) and Malaysia. Therefore, this study examines politicians' use of the Minangkabau and Malay language in Malaysia during the campaign in the two general elections. Data were the political campaign props, such as billboards and banners of competing politicians, available offline (Minangkabau language) and online (Malay language). The study departed from the linguistic landscape and cultural approach. Discussions with politicians regarding using the Minangkabau language in their campaigns were also done. The data were analyzed using the distributional and referential methods. The findings showed that the politicians used the Minangkabau and Malay languages as slogans, warnings, invitations, insinuations, and promises by which they introduced their programs. It was also found that using the Minangkabau and Malay language in campaigning allowed the politicians to build emotional closeness with their potential voters, showing local characteristics and being more communicative as their messages were understood more quickly, especially when emphasizing specific political messages.